(untitled) (Bangladesh Journal of Animal Science, 2019)
A total of 448, Sakini (224) and Giriraja (224) breed of chickens were used to investigate the feed intake & weight gain from 0-150 days and egg production and egg quality from 150 – 240 days of age in Khumaltar Lalitpur Nepal. The four different levels of probiotics viz. 0,5, 10 and 15 ml of Probiotic (Poultry biosa)/kg of feed were used with randomized factor design 2*4*8(RBD) with 8 treatments and 8 replications. The data was recorded daily on feed intake and egg production and in every 15 days interval for weight gain. Results showed that the addition of probiotic to the feed significantly improved feed intake, weight gain , egg production and egg quality on sakini and giriraja breeds of chickens(P<0.05). Additionally, data on egg production and egg quality showed increased production in treatment group than control group (P<0.05).The general trend revealed increasing level of egg production from five to eight months with significant difference (P<0.05). Nutrient analysis of eggs by proximate analysis in terms of CP, CF, fat and energy showed significant difference (P<0.05). Thus to conclude, there is positive effect of probiotics for production and productivity in terms of feed conversion ratio, weight gain, egg production & egg quality in Sakini and Giriraja breed of Chicken. Bang. J. Anim. Sci. 2019. 48 (1): 29-35